FOLDING OF EUROPA'S ICY LITHOSPHERE: AN ANALYSIS OF VISCOUS-PLASTIC BUCKLING AND SUBSEQUENT TOPOGRAPHIC RELAXATION - Dombard A.J.; McKinnon W.B. (My University, 2006)
Potential contractional folds on Jupiter's icy moon Europa have been identified. The best example is at the extensional band Astypalaea Linea, where a series of subtle topographic undulations, 25 km in wavelength, possess parasitic tectonic features that support a folding origin. A scenario has been qualitatively proposed, whereby folds form via unstable contraction of the icy lithosphere, compensate for extension elsewhere on Europa, and then subsequently relax. Here, we quantitatively address this scenario, applying a model for viscous-plastic buckling of planetary lithospheres and finite element simulations of topographic relaxation. Our results suggest that the lithosphere of Europa could indeed be unstable, but the low required surface temperatures limit fold formation to higher latitudes, and the high required driving stresses (~9-10 MPa) are difficult to achieve on the satellite. The depth to the brittle-ductile transition is well constrained, and high thermal gradients are indicated, implying heat flows near 100 mW m-2. In addition, topographic relaxation progresses so slowly even at these heat flows that it is not a viable mechanism to eliminate such features over the age of Europa's surface. Given the paucity of identified folds, we conclude that the necessary conditions for their formation are rare and that lithospheric folding is a minor mechanism for compensating the large amounts of extension seen elsewhere on Europa. © 2005 Elsevier Ltd. All rights reserved.
Keywords: EUROPA; FOLDING; JOVIAN SATELLITES; TECTONICS